Implementation of the Doubling Mamdani Fuzzy Method in Comparing the Output Quality of Four-Wheeled Vehicles in 2024 - Balqis, Muthia Ferliani; Gultom, Abel (Journal of Research in Mathematics Trends and Technology, 2023)
Nowadays, a four-wheeled vehicle or a car is already a primary necessity for most people. Various functions and advantages exist in four wheeled vehicles that are the factors that make the existence of four wheels very helpful in transportation and other activities. As a dynamic means of transportation, four-wheeled vehicles from year to year have been increasing in models and are becoming more and more sophisticated. The problem is that as a prospective buyer, one will surely be confused in choosing a four-wheeled vehicle among its various variations and models. In this paper will be given enlightenment in the selection of four-wheeled vehicles of such variation. Fuzzy decision making, or fuzzy decision maker, with the method of scanning, is designed to help the prospective buyer in selecting the four-wheeled vehicle that meets the criteria of the potential buyer. Based on the criterion desired by the prospecting buyer, the data around the four wheeled vehicles will be processed in the fuzzy assembly system until in the end each of the vehicle four wheels produces fire strength